Evaluation Method of Hydro-wind-photovoltaic Resource Complementarity and Scheduling Complementarity - WU Xinyu; SONG Yuhang; ZENG Boyu; WANG Yuxuan; TIAN Dahui; ZHANG Jiaao (Renmin Zhujiang)
This study addresses the shortcomings in existing research on the evaluation of the scheduling benefits of hydro-wind-photovoltaic complementary systems, particularly the failure to distinguish between the natural complementarity of hydro-wind-photovoltaic resources and the benefits of hydropower compensation in wind- photovoltaic scheduling. Based on discrete differential dynamic programming, an optimal scheduling model is developed for both the hydropower standalone generation system and the hydro-wind-photovoltaic energy complementary system. Two core indicators are proposed: the resource complementarity benefit coefficient and the scheduling compensation benefit index. These indicators establish an evaluation system from two dimensions: natural endowment matching and scheduling strategy optimization. Research in the Hongshui River Basin shows that, at a 95% reliability level, the resource compensation benefit in the basin is 13.56%, while the scheduling compensation benefit is 16.12%. These indicators effectively quantify the significant spatiotemporal complementarity characteristics in the annual distribution of hydro-wind-photovoltaic resources, highlighting the necessity of transforming scheduling methods. This provides a scientific tool for the benefit evaluation of hydro-wind-photovoltaic energy complementary system planning and offers important reference value for the development of new power systems.